Bank re‐erosion action to promote sediment supply and channel diversification: Feedback from a restoration test on the Rhine. (28th March 2022) - Chardon, Valentin; Schmitt, Laurent; Clutier, Anne
Abstract: River regulation alters hydrological and sediment regimes and consequently affects habitat complexity and dynamics, biodiversity and ecosystem services. Although channel bank erosion is a key geomorphological process supplying alluvial channels with coarse sediments and diversifying aquatic and riparian habitats, banks have often been stabilized to limit erosion risk to human activities and facilities. The objective of this paper is to assess the effects, and their sustainability, of bank protection removal on a 300‐m long reach of the Old Rhine (France/Germany) to promote sediment supply, channel diversification and a rehabilitation of fluvial morpho‐sedimentary processes. This action was combined with the construction of two island groynes to locally increase bank erosion processes. Yearly detailed monitoring was implemented over 6 years, including classical bathymetric surveys, airborne topo‐bathymetric and terrestrial LiDAR, and bed grain‐size and bedload tracking. Following a Q15 flood, the restoration induced a weak sediment supply. The restoration diversified habitats due to the implementation of the two island groynes, inducing bank scouring and the creation of new macroforms, as well as local bed grain‐size diversification and fining. The cross‐sectional diversity of the restored water channel was close to the regularization engineering phase. Channel bedform diversification persisted 6 years due to the persistence of the two island groynes. The action induced the rehabilitation of fluvial forms, in a static manner, rather than the rehabilitation of fluvial morpho‐sedimentary processes, which raises questions about the sustainability of the benefits of such management actions in terms of fluvial functionality and naturality.